Literasi Hadis Tentang Larangan Melakukan Kekerasan Terhadap Perempuan - A, Amilianasari; Hafid, Muh. Hasbi; Sakka, Abdurrahman; Khalik, Subehan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research discusses hadiths regarding violence against women. In several hadith narrations, Rasulullah SAW states that there is a prohibition against committing violence (beating) against women. However, another hadith states that it is permissible to hit women, especially wives, but there are certain conditions or limitations that must be met. This is what attracted the attention of researchers in studying the hadith of the Prophet Muhammad Saw. regarding violence against women because there is a contradictory impression in the hadith which is the object of research. This research uses qualitative methods through library research (Library study) by applying Takhrij al-Hadith and Syarah al-Hadith in analyzing the meaning contained in hadith using hadith interpretation techniques. Based on this research, there are three lines of hadith and the quality of the hadith which is the object of research has authentic status because the majority of scholars agree that the book of authentic Bukhari is a hadith book which has authenticity and occupies the position with the highest degree of authenticity among other hadith books and was written by a leading scholar. . The sharah of the hadith which is the object of research is that the hadith gives a warning that if a wife does not carry out the good obligations ordered by Allah, the Messenger of Allah and her husband, it is good. So it is permissible to hit one's wife, but with the intention and aim of educating and not hitting which can damage the psychological and physical body of a woman, especially the wife.